PsychNow! Interactive experiences in psychology - Jeffcoat, Kendra.; Wadsworth/Thomson Learning (Firm) (Wadsworth/Thomson Learning, 2004)
Provides the user with thirty-nine learning modules in eight areas of psychology. Includes research experiments, collaborative labs with chat and discussion groups, multimedia simulation, videos, and quizzes.